2006
DOI: 10.1089/scd.2006.15.305
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Antigen CD34: Role in Adhesion or Homing

Abstract: CD34 is highly glycosylated surface antigen of enormous clinical utility in the identification, enumeration, and purification of engraftable lymphohematopoietic progenitors for transplantation. However, recently its importance in the specific marking of most immature hematopoietic stem/progenitor cells have been questioned by addressing long-term reconstitution capability of CD34(-) hematopoietic cellular fractions. These controversies have stimulated a demand for elucidation of the structure, function, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 63 publications
3
47
0
Order By: Relevance
“…They were also positive for surface markers such as CD13, CD44, CD59, CD73, CD90, CD105 and CD166 [Gronthos et al, 2001;Lee et al, 2004;Wagner et al, 2005;Dominici et al, 2006]. CD34, a haematopoietic marker described as a negative marker for MSCs [Dominici et al, 2006], was not expressed in bone marrow-derived MSCs, which is in keeping with the results obtained by other groups [Gangenahalli et al, 2006]. In adipose tissue-derived MSCs at P1, this marker was expressed in up to 15% of cells ( fig.…”
Section: Discussionsupporting
confidence: 87%
“…They were also positive for surface markers such as CD13, CD44, CD59, CD73, CD90, CD105 and CD166 [Gronthos et al, 2001;Lee et al, 2004;Wagner et al, 2005;Dominici et al, 2006]. CD34, a haematopoietic marker described as a negative marker for MSCs [Dominici et al, 2006], was not expressed in bone marrow-derived MSCs, which is in keeping with the results obtained by other groups [Gangenahalli et al, 2006]. In adipose tissue-derived MSCs at P1, this marker was expressed in up to 15% of cells ( fig.…”
Section: Discussionsupporting
confidence: 87%
“…The vast majority of studies on CD34 have focused on its presence in the hematopoietic system (for review, see Refs. 15,16,21,23), where this antigen is known to mark nonquiescent cells involved in migration or proliferation, but is absent in terminally differentiated lineages (8,19). Only a handful of studies have looked at vascular expression of CD34, where it has been reported to be widely expressed on the endothelium of blood vessels in normal human and mouse adult (3,14,18,24,37) and fetal (14,50,51) tissues, as well as on lymphatic endothelium in humans (13,41).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that only 5.5 ± 2.3% (mean ± SD) of CD34+ cells homed to the myocardium after intracoronary injection in 6 patients [41]. Although its precise structure and function remain poorly understood [42], these data suggest that CD34 might be involved in the migration of stem cells. Specific selection of this CD34+ cell type might turn out to be beneficial for stem cell therapy [43].…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…Specific selection of this CD34+ cell type might turn out to be beneficial for stem cell therapy [43]. Some have even suggested manipulating CD34 or its interactions to enhance therapy efficiency [42]. …”
Section: Stem Cell Therapymentioning
confidence: 99%